Modeling the transport and anisotropy of energetic electrons in solar flares - Kong, Xiangliang; Ning, Hao; Chen, Yao (Frontiers in Astronomy and Space Sciences, 2025)
Transport of energetic electrons in the flare loop is important to understanding nonthermal emissions in solar flares. In this work, we model the propagation of electrons by numerically solving the particle transport equation which includes the physics of magnetic mirroring and turbulent pitch-angle diffusion. We find that both the fractions of electrons trapped in the looptop and precipitating into the solar surface display a non-monotonic behavior with increasing scattering rate. In the moderate diffusion regime, the precipitation fraction is highest and we expect intense nonthermal HXR and microwave emissions at the footpoints. With no or weak pitch-angle scattering, the velocity space distribution can be highly anisotropic both in the looptop and loopleg regions. Different patterns of stripes with positive gradients in the perpendicular direction can drive the electron cyclotron maser instability with higher efficiency than the classical loss-cone distribution, facilitating the excitation of coherent solar radio bursts. Our simulation results highlight the effects of turbulent pitch-angle scattering on electron trap/precipitation and anisotropic distribution in solar flares, which may help us understand the precipitation of magnetospheric electrons accounting for the aurora as well.